Purine-Induced IFN-γ Promotes Uric Acid Production by Upregulating Xanthine Oxidoreductase Expression - Wang, Huanhuan; Xie, Lingzhu; Song, Xuhong; Wang, Jing; Li, Xinyan; Lin, Zhike; Su, Ting; Liang, Bin; Huang, Dongyang (Frontiers in Immunology, 2022)
Objective: Limiting purine intake and inhibiting xanthine oxidoreductase (XOR), to reduce uric acid (UA) levels, are recognized treatments for gout. However, the mechanism of increased XOR expression and activity in hyperuricemia and gout remains unclear. This study aims to explore whether exogenous purines are involved in the mechanism of increased XOR expression and activity. Methods: HepG2 and Bel-7402 human hepatoma cells were stimulated with purine followed by measurement of XOR expression and UA production, or were exposed to medium from purine-stimulated Jurkat cells to determine the effect of lymphocyte-secreted cytokines on XOR expression in hepatocytes. The expression of STAT1, IRF1 and CBP and their enrichment on the XDH promoter were detected by western blotting and ChIP-qPCR. The level of DNA methylation was detected by BSP. Blood samples from 236 hyperuricemia patients and healthy individuals were collected to analyze the correlation between purine, UA and IFN-γ concentrations. Results: Excessive purine was converted to UA through hepatocyte metabolism, but did not directly induce XOR expression. Instead, purine induced XOR expression indirectly by enhancing the production of IFN-γ in Jurkat cells. IFN-γ upregulated XOR by promoting the binding of STAT1 to IRF1 to further recruit CBP to the XDH promoter. Clinical data showed that serum IFN-γ was positively correlated with both purine and UA, and high levels of IFN-γ were associated with risk of hyperuricemia. Conclusion: Purine not only acts as a metabolic substrate to produce UA, but also induces inflammation and activates the purine metabolic pathway to promote further UA production.